University proceedings. Volga region. Natural sciences - O.V. Chernyshova; N.A. Kartavov; R.A. Ilyin; S.V. Titov (Известия высших учебных заведений. Поволжский регион: Естественные науки)
Background. The study of the consequences of natural interspecific hybridization of closely related species in secondary contact zones is one of the urgent tasks of evolutionary biology. As the conducted studies of ground squirrels hybrids show, their inheritance of the characteristics of the parent species is not only intermediate in nature. Depending on the succession in the further crossing of hybrid individuals and the participation in this process of individuals of one (or both) of the parent species, a heterogeneous combination of characteristics of the parent species occurs. The purpose of the work was to study individuals of speckled (Spermophilus suslicus Guld.) and large (S. major Pall.) ground squirrels from the sympatric zone in the Volga region using a complex of molecular genetic markers, color indicators and acoustic signal parameters in order to identify cases of introgression of foreign DNA. In addition, one of the objectives of the research was to identify potential parental colonies of S. suslicus for further work on the restoration of colonies of this species in the region. Materials and methods. On the territory of Ulyanovsk region 9 colonies were surveyed: 6 combined and 6 single–species colonies were surveyed: 6 – joint (characterized by separation of species by microstations), 3 – mixed (without separation), 3 – S. suslicus and 3 – S. major. 60 individuals of both species and possible interspecific hybrids were captured and tagged in the colonies Molecular genetic studies were performed on 5 markers (D-loop, Hoxb5, p53, ZfX, SmcY). The sound signals and color indicators of 11 large, 11 speckled ground squirrels, 5 interspecific hybrids and female speckled ground squirrels 2036* were analyzed. Statistical data processing was carried out in the STATISTICA 10.0 program. Results. A study of 29 individuals of the large and 31 individuals of the speckled ground squirrel from the sympatry zone in Ulyanovsk region showed that only one female, certifiedaccording to phenotypic characteristics as S. suslicus, had introgression of S. major genetic material. During the analysis of color and acoustic signs, the special genetic status of the female speckled ground squirrel 2036* was shown. It cannot be recognized unambiguously as a hybrid individual, even in the status of a hybrid with combined inheritance of traits of parent species (Hcomb), which we described in detail earlier. We are probably dealing with a case of either a much repeated backcrossing of a hybrid individual with speckled ground squirrel individuals, or the manifestation of S. major genes in the speckled ground squirrel genotype. Conclusions. The results of the research revealed the first case of introgression of S. major genes into the genotype of the speckled ground squirrel. At the same time, we note that the reverse situation – introgression of S. suslicus genes into the genotype of the large ground squirrel, outside the boundaries of hybrid colonies, in single-species colonies of S. major, was not detected by us during the entire observation period (30 years). In general, such a development of the relationship between speckled and large ground squirrels in the sympatry zone, which has existed for 70 years on the territory of the right-bank Volga region, associated with the fixation of foreign genes in the genotypes of speckled ground squirrels, imposes a number of restrictions on the planned research. Genotyping of individuals in single-species populations of speckled ground squirrel in the right-bank Volga region at the present stage is becoming a prerequisite for successful research and rehabilitation measures.